2006
DOI: 10.1021/bi060106s
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Two-Step Mechanism Involved in the Formation of Covalent HC·TSG-6 Complexes

Abstract: IalphaI and TSG-6 interact to form a covalent bond between the C-terminal Asp alpha-carbon of an IalphaI heavy chain (HC) and an unknown component of TSG-6. This event disrupts the protein-glycosaminoglycan-protein (PGP) cross-link and dissociates IalphaI. In simple terms the interaction involves 5 components: (i) the IalphaI HCs, (ii) bikunin, (iii) chondroitin sulfate chain, (iv) TSG-6, and (v) divalent cations. To understand the molecular mechanism of complex formation, the effect of these were separately e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
48
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 25 publications
(57 reference statements)
4
48
3
Order By: Relevance
“…1, lanes 1 and 3). Previously, it has been shown that the HC transfer reaction is HC2-and divalent cation-dependent (14,16,28). Therefore, samples without HC2 or without divalent cations were used as negative controls, and as expected, no HC transfer was observed in these samples (Fig.…”
Section: Comparison Of the Authentic Hc Position On The Cs And The Hcsupporting
confidence: 55%
See 2 more Smart Citations
“…1, lanes 1 and 3). Previously, it has been shown that the HC transfer reaction is HC2-and divalent cation-dependent (14,16,28). Therefore, samples without HC2 or without divalent cations were used as negative controls, and as expected, no HC transfer was observed in these samples (Fig.…”
Section: Comparison Of the Authentic Hc Position On The Cs And The Hcsupporting
confidence: 55%
“…HMW I␣I was also degraded by chondroitinase ABC, indicating that the HCs similarly had been rearranged. Moreover, inhibition of the TSG-6/HC2 transfer activity (14,28) prevented chondroitinase ABC from cleaving and releasing the two HCs, supporting that the authentic position was maintained (Fig. 3, lane 4).…”
Section: Comparison Of the Authentic Hc Position On The Cs And The Hcmentioning
confidence: 59%
See 1 more Smart Citation
“…The plasma was obtained from Statens Serum Institut, Copenhagen, Denmark. CS substituted bikunin was purified from NaOH-dissociated I␣I as described recently (14). Human TSG-6 was expressed in insect cells and purified as described before (19).…”
Section: Methodsmentioning
confidence: 99%
“…The formation of these complexes involves a twostep process in which TSG-6 and the CS chain of bikunin initially interact in a divalent cation-independent way (14). Subsequently the HC⅐TSG-6 complexes are formed during a divalent cation-dependent transesterification reaction (14).…”
mentioning
confidence: 99%